MANAGEMENT STRATEGY FOR PANDAN BEACH MARINE TOURISM, CENTRAL TAPANULI REGENCY, NORTH SUMATRA - Ferya Lufika Br Simaremare; Trisla Warningsih; Tomi Ramadona (Asian Journal of Aquatic Sciences, 2026)
Pandan Beach is a popular tourist destination in Central Tapanuli Regency. The number of tourists in 2018 was 184,355; in 2019, it decreased to 114,925; in 2020, it decreased to 90,240; in 2021, it increased to 123,905; and in 2022, it decreased to 63,191. This research was conducted at Pandan Beach, Central Tapanuli Regency, North Sumatra Province, in May 2023. This study aims to determine the current conditions and management strategies for Pandan Beach. The method used in this research is the survey method. The sample in this study amounted to 100 respondents. In this study, informants included 3 managers from Pandan Beach, Bappeda, and the Tourism Office, a Village Head, and 2 community leaders. The data obtained were analyzed using descriptive and SWOT analyses. The results of this study indicated that the appropriate management strategy for Pandan Beach is the SO (Strengths-Opportunities) strategy. Utilizing the natural beauty of Pandan Beach to attract tourists to visit, improving the quality and quantity of existing facilities such as toilets, prayer rooms, and others, utilizing government support to support the management of Pandan Beach attractions, involving surrounding communities, such as fishermen, to increase income and increase fishermen's income through boat rental and photo both.